Immediate rehabilitation of a palatal defected edentulous patient by implant-supported overdenture: a case report - Baojian Xin; Xin Liu (BMC, 2024)
Abstract Background Immediate rehabilitation is a considerable therapeutic challenge but is necessary for edentulous patients with oronasal fistulas, especially those with inadequate residual bone and a history of radiotherapy. Case presentation We report a rare case of a 63-year-old patient who was missing the majority of his maxillary teeth and who had a defect due to palatal mucoepidermoid carcinoma resection. The patient also received radiotherapy twice within one year postoperatively. An implant-supported prosthesis with an obturator was fabricated immediately. Conclusion This technique improved patients' oral function, enhanced the aesthetic effect, and increased their confidence.